Evaluation of Judicial Procedure in the Essence of the Method of the Wise - Moein Gholamalipour; Ahmad Bagheri (پژوهشهای حقوقی, 2024)
Frequent judicial decisions in similar cases are known as judicial procedure. This event, as one of the sources of law, has a significant role in the development and excellence of the rights of societies. But one of the questions that has always been asked is why judicial procedure in the general sense has not had a proper place in Iranian law? Since Iranian law originates from Islamic jurisprudence, the reason for this is the incompatibility of jurisprudence with Islamic rules, to the extent that a number of jurists have denied the principles of jurisprudence in Islamic law. While examining the conduct of the wise and its authority from the perspective of Imam Khomeini and some experts, the functions of the judicial procedure were also explained. It is considered and thus can not be considered an obstacle to the application of judicial procedure in the general sense (rule-making procedure) in the Iranian judicial system.